Social privileges in the Second Polish Republic - Grata, Paweł (Studia Historiae Oeconomicae, 2015)
The Second Polish Republic developed an advanced and, in many ways, modern system of social care; however, the services which the citizens were entitled to seemed to be privileges available only to a small part of the population. The origins of this situation are to be found in the specific social and occupational structure of the population, low industrialization rate and the modest financial capabilities of the state and local governments. These resulted in a limited number of people with access to social insurances, a limited scope of public health care, a selective nature of access to unemployment insurance or radical differences in access to social care. And it is this unavailability of the social offer which determines the consideration of those benefits in Poland as privileges rather than commonly available rights of the Polish citizens.